The conversational organization of musical contributions. (November 2014) - Duffy, Sam; Healey, Patrick G. T.
There are many ways that people come together for the purpose of making music, each offering different opportunities for interaction and exhibiting different communicative characteristics. Through the study of one-to-one instrumental music lessons featuring the clarinet, we find that student and tutor musical contributions are organized using aspects of conversational turn-taking. Short fragments of music, which are characteristic of lesson activity, can also function as turns in themselves as student-tutor dialogue unfolds. When the medium for communication is changed and we analyse video mediated music lessons, these mechanisms are less effective, revealing the importance of this organization to lesson flow, and to musical interaction more generally.